Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) Konstruksi pada Proyek Pembangunan Gedung Sekolah SD Negeri 7 Bengkulu Tengah - Sofyan Ansori; Rezi Munizar (Journal of Science, Technology, and Innovation, 2026)
The construction industry has a high rate of workplace accidents, making the implementation of Occupational Safety and Health (OSH) a fundamental aspect of project success. This study aims to analyze the level of OSH implementation, identify factors hindering implementation, and formulate strategies to improve safety in the Construction Project of the State Elementary School No. 7 in Central Bengkulu. The research method employed a mixed-methods approach through field observations based on the SMKK checklist and a Likert-scale questionnaire administered to 30 respondents, consisting of project management, foremen, and construction workers. The results showed a 63% compliance rate with OSH implementation, categorized as “adequate,” while the use of secondary PPE, emergency response facilities, and safety supervision were identified as areas requiring improvement. The main inhibiting factors include low worker discipline, limited supervision, and suboptimal safety education. The study recommends strengthening the safety culture through routine training, periodic inspections, and work-activity-based risk control to support the achievement of safe construction.